2022
DOI: 10.3390/su142315955
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Systems and Sustainability. Development of a Methodology on Innovation Systems for the Measurement of Sustainability Indicators in Regions Based on a Colombian Case Study

Abstract: In recent years, the need for changes in the current consumption and development patterns has become evident. To achieve this, it is necessary to innovate, create, and devise new methodologies and ways of thinking that allow for a reorientation towards economically prosperous, socially equitable, and environmentally reasonable practices. The purpose of this study is to identify sustainability variables within the framework of the innovation system concept, and to propose a methodology for diagnosing regions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
0
4
0
1
Order By: Relevance
“…The aim of the study (Sossa et. al., 2022) was to identify variables within the framework of the innovation system concept, as well as the methodology for their diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the study (Sossa et. al., 2022) was to identify variables within the framework of the innovation system concept, as well as the methodology for their diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is reinforced by the conceptualization of Lee, W.J. ; Mwebaza, R. cited by Zartha [6] where it indicates that innovation can be defined as the result of a set of activities that use knowledge, skills, and/or technologies to satisfy individual or social needs.…”
Section: Methodsmentioning
confidence: 99%
“…Zartha Sossa et al ( 40 ) have investigated the effects of an innovation system for attaining sustainability in the Colombian region. Their study indicated that there is a lack of disarticulation between the policies related to sustainability in the innovation system which may amplify economic development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Keeping all political and sectarian disputes aside, political leaders should join hands for the prosperity and development of their nations. Innovation is an ongoing process and SOIS reflects that innovation which is decoupling economic growth from environmental pressures ( 40 ). Silvestre and Ţîrcă ( 38 ) have concentrated on the promotion of innovation due to its role in transforming individuals, societies, organizations, and communities.…”
Section: Literature Reviewmentioning
confidence: 99%